Sombras da justiça no cinema hollywoodiano - Silva Neto, Artur Marques da (2007)
The present study investigates the construction of effects of sense of justice in Hollywood movies, more specifically those that have as main plot courtroom trials. The relevance of the work surfaces from the influence that the cultural production, directed towards the mass exerts has in the setting of ideologies and the maintenance of the legal institutions as source of coordination of the conviviality in society. Through the analysis of the simulacrum of judgments personified in the films and it focus on the tension between justice and law, the work reconstructs the different impressions of reality produced by our senses and discuss how the reception of this effect of sense of justice is made by the spectator. Considering that the central problematic of the work was the analysis of the sense produced in the films, it was proved that the methodology of the gerative course of sense based on the Discursive Semiotics from Algirdas Julien Greimas and its collaborators, would be of great use as a source for our investigation process. We privilege as selected corpus, the deconstruction of the films, displaying sequences that summarized the essence of all the sense of the text, those were occur the description of the legal facts in ponder and its developments until the outcome of the workmanship. The selection and cuts of the research corpus uses as parameters: the similarity of themes between the pictures, corroborating with the proposal of scientific interdisciplinary; the production s reach (public); the model of construction; the explicit invariable aspects and dissimilarities in the discursive level between the films. For this reason, the searched corpus is composed by the films A Few Good Men (Questão de Honra, 1992), And Justice for All (Justiça para Todos, 1979) and Primal Fear (Duas Faces de um Crime, 1996), Sacco e Vanzetti (Sacco e Vanzetti, 1971). By the film analyses, for the effect of sense of justice, the category of just must became a evidence of the truth inside the legal procedure. Moreover, it was observed that, independent of the effect of sense of justice enunciated in the basic level, the values that the social ordinance always keeps are gifts